2018
DOI: 10.1186/s12968-018-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-center clinical validation and quantitative assessment of respiratory triggered retrospectively cardiac gated balanced-SSFP cine cardiovascular magnetic resonance imaging in adults

Abstract: BackgroundBreath-hold (BH) requirement remains the limiting factor on the spatio-temporal resolution and coverage of the cine balanced steady-state free precession (bSSFP) cardiovascular magnetic resonance (CMR) imaging. In this prospective two-center clinical trial, we validated the performance of a respiratory triggered (RT) bSSFP cine sequence for evaluation of biventricular function.MethodsOur study included 23 asymptomatic healthy subjects and 60 consecutive patients from Institute A (n = 39) and Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Third, although the single slice‐based estimation of diastolic function indices (basal slice for V EFP /V LFP , and mid LV slice for R EFP /R LFP ) correlated well with indices extracted from the entire LV volume, it remains to be determined whether such correlations are valid in patients with regional wall motion abnormalities. Furthermore, a recent study has shown that the free‐breathing cine MRI method used in this study takes longer (about 3 min) and that the image quality—although diagnostic—is slightly inferior to that of conventional breath‐hold cine imaging . Further studies are necessary to evaluate whether recent advances in spatiotemporal undersampling methods such as compressed sensing may be used to partly or fully address the issue of longer scan times.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Third, although the single slice‐based estimation of diastolic function indices (basal slice for V EFP /V LFP , and mid LV slice for R EFP /R LFP ) correlated well with indices extracted from the entire LV volume, it remains to be determined whether such correlations are valid in patients with regional wall motion abnormalities. Furthermore, a recent study has shown that the free‐breathing cine MRI method used in this study takes longer (about 3 min) and that the image quality—although diagnostic—is slightly inferior to that of conventional breath‐hold cine imaging . Further studies are necessary to evaluate whether recent advances in spatiotemporal undersampling methods such as compressed sensing may be used to partly or fully address the issue of longer scan times.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a recent study has shown that the free-breathing cine MRI method used in this study takes longer (about 3 min) and that the image quality-although diagnostic-is slightly inferior to that of conventional breath-hold cine imaging. 22 Further studies are necessary to evaluate whether recent advances in spatiotemporal undersampling methods such as compressed sensing may be used to partly or fully address the issue of longer scan times. High frame rate cine imaging requires additional time for the cardiovascular imager to segment the LV cavity, which may be partly reduced with semiautomatic or automatic LV contour analysis tools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerated cine CMR techniques (such as k-t BLAST, TPAT, TSENSE, and compressed sensing) have reported bias in left ventricular (LV) volumes, function, and LV mass due to spatiotemporal blurring and temporal filtering [20][21][22][23][24][25][26]. Free-breathing (FB) respiratory triggered retrospectively cardiac gated cine bSSFP sequences have been reported to provide biventricular volumes, function, and LV mass comparable to BH acquisitions with a SENSE acceleration factor of 2 in adults and children [27,28]. With the goal of accelerating SENSE, a compressed sensitivity encoding (C-SENSE) algorithm was developed that employs a pseudorandom undersampling of k-space in the spatial domain.…”
Section: Introductionmentioning
confidence: 99%